First Clinical Experience With the Pressure Sensor–Based Autoregulation of Blood Flow in an Artificial Heart. Issue 10 (October 2021) - Netuka, Ivan; Pya, Yuriy; Poitier, Bastien; Ivak, Peter; Konarik, Miroslav; Perlès, Jean-Christophe; Blažejová, Zuzana; Riha, Hynek; Bekbossynova, Makhabbat; Medressova, Assel; Bousquet, Fabien; Latrémouille, Christian; et al.
Abstract : The CARMAT-Total Artificial Heart (C-TAH) is designed to provide heart replacement therapy for patients with end-stage biventricular failure. This report details the reliability and efficacy of the autoregulation device control mechanism (auto-mode), designed to mimic normal physiologic responses to changing patient needs. Hemodynamic data from a continuous cohort of 10 patients implanted with the device, recorded over 1, 842 support days in auto-mode, were analyzed with respect to daily changing physiologic needs. The C-TAH uses embedded pressure sensors to regulate the pump output. Right and left ventricular outputs are automatically balanced. The operator sets target values and the inbuilt algorithm adjusts the stroke volume and beat rate, and hence cardiac output, automatically. Auto-mode is set perioperatively after initial postcardiopulmonary bypass hemodynamic stabilization. All patients showed a range of average inflow pressures of between 5 and 20 mm Hg during their daily activities, resulting in cardiac output responses of between 4.3 and 7.3 L/min. Operator adjustments were cumulatively only required on 20 occasions. This report demonstrates that the C-TAH auto-mode effectively produces appropriate physiologic responses reflective of changing patients' daily needs and represents one of the unique characteristics of this device in providing almost physiologic heart replacement therapy.